Agriculture pesticides use as tool for monitoring health hazards - Bravo Durán, Virya (2013)
In Costa Rica the use of toxic pesticides has increased. This is mainly due to the development of resistant pests, and the need for certain agricultural export products to maintain its position in the international marketplace. Humans when in contact with pesticides can experience adverse health effects, ranging from acute to chronic and that manifest in different degrees. To generate indicators of the hazards arising in the human health posed by the use of these substances in some crops, the amount of pesticides applied and their toxicity was used. Data of pesticide use were collected directly from producers, through a questionnaire. The active ingredients identified were characterized in accordance with their toxicity and classified according to the manifestation of the effects. The indicators used were the amount of pesticides applied (kg ai / ha / year) for the most considered toxic class: 1-effects for acute toxicity on high-grade and, 2- the pesticides with three or more positive chronic effects. It is recommended to monitor the use of methyl bromide, metam sodium, terbufos, ethoprophos, endosulfan, MCPA and carbofuran for high to extreme acute toxicity, and the one of mancozeb, paraquat, diazinon, 2,4-D and carbofuran for chronic effects.